Manfaat Pembelajaran Olah Tubuh Dalam Membentuk Wiraga Seorang Penari Di Sanggar Sak Sak Dance Production Kota Mataram Nusa Tenggara Barat - Ariani; Ria Taurisia Armayani, Ni Made; Prajawati, Yani Timor (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
This research is to describe the benefits of body exercise learning in forming wiraga a dancer's dance production. The background of this research is that body movements are very influential on the wiraga of professional dancers, namely to form wiraga dancers, prepare the body for movement, flexibility, strength, endurance, endurance and breathing with the many benefits of exercise training, but there are still many professional dancers who have not know it, and this research aims to form wiraga a professional dancer. This study uses descriptive qualitative research, with the data sources used are primary data obtained from interviews of trainers and students and secondary data obtained from library data: books, theses, and journals. Data collection techniques used are non-participant observation, structured interviews, documentation and then analyzed in stages, namely data reduction, data presentation and conclusion drawing. The results of the study can be concluded that 1) The learning process for bodybuilding in the sak sak dance production is divided into several stages, namely: warm-up exercises, core exercises, cooling exercises and balance exercises with a training time of 10-30 minutes, 2) Obstacles in learning exercise in the studio sak sak dance production , namely there are some movements that are too difficult such as kayaking, split, roll and body balance, mood changes and movement equations, 3) The benefits of learning body exercise in the sak sak dance production are being able to shape, flex the body, endurance, balance, endurance, student skills and very influential on student achievement in dance competitions and events and can make the province of West Nusa Tenggara proud;